Iodination of cyclo‐E5‐Complexes (E=P, As). Issue 37 (9th July 2020) - Brake, Helena; Peresypkina, Eugenia; Virovets, Alexander V.; Piesch, Martin; Kremer, Werner; Zimmermann, Lisa; Klimas, Christian; Scheer, Manfred
Abstract: In a high‐yield one‐pot synthesis, the reactions of [Cp*M(η 5 ‐P5 )] (M=Fe (1 ), Ru (2 )) with I2 resulted in the selective formation of [Cp*MP6 I6 ] + salts (3, 4 ). The products comprise unprecedented all‐ cis tripodal triphosphino‐cyclotriphosphine ligands. The iodination of [Cp*Fe(η 5 ‐As5 )] (6 ) gave, in addition to [Fe(CH3 CN)6 ] 2+ salts of the rare [As6 I8 ] 2− (in 7 ) and [As4 I14 ] 2− (in 8 ) anions, the first di‐cationic Fe‐As triple decker complex [(Cp*Fe)2 (μ, η 5:5 ‐As5 )][As6 I8 ] (9 ). In contrast, the iodination of [Cp*Ru(η 5 ‐As5 )] (10 ) did not result in the full cleavage of the M−As bonds. Instead, a number of dinuclear complexes were obtained: [(Cp*Ru)2 (μ, η 5:5 ‐As5 )][As6 I8 ]0.5 (11 ) represents the first Ru‐As5 triple decker complex, thus completing the series of monocationic complexes [(Cp R M)2 (μ, η 5:5 ‐E5 )] + (M=Fe, Ru; E=P, As). [(Cp*Ru)2 As8 I6 ] (12 ) crystallizes as a racemic mixture of both enantiomers, while [(Cp*Ru)2 As4 I4 ] (13 ) crystallizes as a symmetric and an asymmetric isomer and features a unique tetramer of AsI arsinidene units as a middle deck. Abstract : The iodination of cyclo ‐E5 complexes was introduced for the synthesis of polypnictogen complexes. In the reaction of [Cp*M(η 5 ‐P5 )] (M=Fe, Ru) with iodine, [Cp*MP6 I6 ] + cations with tripodal cyclo ‐{P(PI2 )}3 ligands were formed. With cyclo ‐As5 complexes, the first di‐cationic Fe‐As triple decker, the first monocationic Ru‐As5 triple decker and two isomers of a complex with a unique tetramer of iodoarsinidene units were obtained.